Теоретичні основи та практичні методи визначення надійності діяльності водія в містах у темну пору доби - Прасоленко, Олексій (Посвіт, 2019)
The practical methods of driver's reliability in cities at night was determinated.
Theoretical frameworks and practical methods for determination of driver's reliability in cities at night
Keywords: 656.13–051; 159.91